Financial Literature Education to Improve Minimum Competency Assessment - Rukdianti Aslinda Asnur (Budapest International Research and Critics University, 2022)
The aim of this research is to increase the minimum competence of students through the implementation of financial literacy education. The research method used in this research is descriptive qualitative method. The type of data used in this study is qualitative data, which is categorized into two types, namely primary data and secondary data. Sources of data obtained through library research techniques (library studies) which refers to sources available both online and offline such as: scientific journals, books and news sourced from trusted sources. Based on the description analysis above, it can be concluded that financial literacy education that can be provided can be done by: a) Financial literacy education with a financial literacy car (SiMOLEK); b) Simulation of banking products; c) Oral and written socialization; d) Preparation of educational curriculum design that contains material on financial literacy.